Digital transformation of the chinese banking sector - Li, Rong (БНТУ, 2023)
The article examines the impact of WeChat and Alipay on traditional banking, highlighting their ability to provide real-time interactions and services. QR code payments have become popular and surpassed traditional banks. Although traditional banks have introduced mobile banking platforms, they still lag behind Alibaba and Tencent. Some banks, like China Construction Bank, have launched their own e-commerce platforms and personalized recommendations using user data. The study explores the survival of traditional banks in the digital era and offers insights into the future development of traditional banks and other financial industries.